Correlation of serum leptin with levels of hemoglobin in hemodialysis - Rafieian-Kopaei, Mahmoud (J Nephropharmacol, 2012)
To examine the association of serum leptin level with anemia in hemodialysis, we investigated 36 patients (males: 21, diabetics: 11) under regular hemodialysis. For patients, complete blood counts, iron profile, serum leptin, and adequacy of hemodialysis were assessed. In this study a significant correlation of serum leptin with level of hemoglobin and body mass index was detected. An association between serum leptin and total iron binding capacity was observed. No correlation of serum ferritin with leptin level was seen. Our findings attest previous findings showing that greater serum leptin levels are associated with greater hemoglobin levels.